Improving Communication in Running a Lean Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): How can proper or effective communication of a leader affect employees of a slender organisation?Purpose: The purpose of the research is to determine what leaders can do in communicating to the chosen goal. We are exploring what good communication between the employee and the manager means and the way we communicate. A key objective of a lean organization is to better track perfection, which is difficult to provide. All participants must strive to improve processes, optimise equipment and improve quality.Method: We used a quantitative method, we came from known sources. We also used our own experience from the organization as an employee as well as a leader and lectures outside and in the selected organization.Results: The results of the survey show that the leader is largely responsible for good and effective communication. With proper communication, it gives an example to employees, better understanding and, consequently, greater quality of work and motivation. Communication in an organization is one of the most important things that contributes to a good working environment.Organization: The organization would be better connected and uniform with real communication, while also increasing the quality of work. Tracking in the market may increase the flexibility and speed of product production. Employees, however, would still be motivated to work.Society: Aspects of the social dimension of the quality of communication and leanness are based on proper communication. With proper communication, it can create confidence, proper handing over and sharing of work, while also maintaining suggestions, initiatives and even criticism from employees.  The focus on leanness is that everything is done as easily and quickly as possible. Cooperation, teamwork and approach play a key role in this. At the same time, the quality, efficiency and performance of the company are increased.Originality: Research shows that communication has a very high importance in leadership. With the desire to run a slender company that is flexible and successful, the manager must focus on important information, while providing sufficient information about the work.Limitations/Future Research: For a broader view of the impact of communication in leadership, we should survey both managers and employees. At the same time, it would make sense to examine several organisations and literature.
Keywords: lean organization; communication; leadership; impact on employees; motivation; quality of work